2016
DOI: 10.1002/icd.2018
|View full text |Cite
|
Sign up to set email alerts
|

Seeing and knowing: Attention to illustrations during storybook reading and narrative comprehension in 2‐year‐olds

Abstract: Research (Evans & Saint‐Aubin, ) suggests systematic patterns in how young children visually attend to storybooks. However, these studies have not addressed whether visual attention is predictive of children's storybook comprehension. In the current study, we used eye‐tracking methodology to examine two‐year‐olds' visual attention while being read an unfamiliar storybook. Immediately following reading, they completed a comprehension assessment. Children who visually attended to illustrations depicting key narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…Children who know some basic facts about a certain topic may have a cognitive structure of information that allows even the brief introduction of vocabulary words that are common in storybooks to be integrated into the overall schema for that topic. This study also supports and extends research, suggesting that background knowledge may act as a mechanism to guide of visual attention (Kaefer, Neuman, & Pinkham, in press; Evans & Saint‐Aubin, ). For children without a strong semantic framework of background knowledge, there may simply be too much new information to correctly direct attention, whereas those with relevant knowledge may be able to quickly orient to unknown elements.…”
Section: Discussionsupporting
confidence: 87%
“…Children who know some basic facts about a certain topic may have a cognitive structure of information that allows even the brief introduction of vocabulary words that are common in storybooks to be integrated into the overall schema for that topic. This study also supports and extends research, suggesting that background knowledge may act as a mechanism to guide of visual attention (Kaefer, Neuman, & Pinkham, in press; Evans & Saint‐Aubin, ). For children without a strong semantic framework of background knowledge, there may simply be too much new information to correctly direct attention, whereas those with relevant knowledge may be able to quickly orient to unknown elements.…”
Section: Discussionsupporting
confidence: 87%
“…More contemporary research has observed that children at the age of 4 years begin to understand cross-panel continuity and activity cues, reaching full understanding between 5 and 6 years (Bornens, 1990). These ages align with the shift from children describing isolated image units to narrating sequential events (Berman, 1988;Karmiloff-Smith, 1985;Paris & Paris, 2003;Poulsen et al, 1979;Shapiro & Hudson, 1991;Trabasso & Nickels, 1992;Trabasso & Stein, 1994). Children between 4 and 6 years also increasingly select accurate sequence-ending panels (Zampini et al, 2017), and are moderately good at discerning the causes or consequences of a sequence's main event (A. L. Brown & French, 1976).…”
Section: Development Of Sequential Image Comprehensionmentioning
confidence: 90%
“…Researchers rarely analyze or acknowledge these visual narrative structures (cf. Berman & Slobin, 1994;Trabasso & Nickels, 1992), or the processes necessary to understand them (e.g., Karmiloff-Smith, 1985), despite them laying the foundation for all subsequent interpretations.…”
Section: Caveats For Researchmentioning
confidence: 99%
“…Pesquisas mostram que crianças pré-escolares passam a maior parte do tempo olhando para as ilustrações do livro em um episódio de leitura compartilhada e que sua inspeção à ilustração, em geral, corresponde aos elementos que aparecem na história (Evans & Saint-Aubin, 2013). Além disso, a atenção às ilustrações de um livro durante sua leitura está positivamente correlacionada com a aprendizagem de palavras contidas na história e à compreensão do enredo (Kaefer, Pinkham & Neuman, 2017). Nesse sentido, se as ilustrações de um livro claramente apresentam figuras relacionadas às palavras que aparecem na história, a aprendizagem de novas palavras é facilitada (Evans & Saint-Aubin, 2013).…”
Section: Introductionunclassified